골관절염 치료의 최근 문제 - 박준용; 이성원 (Taehan Ŭisa Hyŏphoe chi, 2024)
Background: Osteoarthritis (OA) is the most prevalent chronic joint disorder that leads to pain, disability, and functional impairment. The OA prevalence among those aged ≥65 years in Korea was 30.2% between 2017 and 2021. Owing to a rapidly aging population, OA is becoming a significant public health and socioeconomic concern. Current Concepts: The onset of OA is characterized by cartilage injury, which affects the surrounding tissues and progresses to joint destruction. The pathophysiology varies across joints; hand OA is associated with genetic factors, whereas knee and hip OA are associated with mechanical stress. Nonsteroidal anti-inflammatory drugs are the primary treatment; however, considering their adverse effects and limited efficacy in halting disease progression, further research is warranted for more effective therapies. Natural medicines have been investigated; however, their clinical efficacy is inadequate. Discussion and Conclusion: Currently, no disease-modifying treatments are validated for OA. Animal models fail to reflect the slow progression and complexity of human OA; therefore, drug development remains challenging. In view of increasing healthcare costs and rapid population aging, further research and broader socioeconomic strategies are essential to manage the growing burden of OA. KCI Citation Count: 0